Exploring aspects of the cognitive behavioural model of physical hoarding in relation to digital hoarding behaviours. (October 2019) - Thorpe, Susan; Bolster, Alexander; Neave, Nick
While the hoarding of physical objects has been extensively explored, there is little research relating to the hoarding of digital materials. The research that has been conducted suggests that digital hoarding (DH) behaviours appear to have some similarities with physical hoarding (PH) behaviours, and can be just as psychologically distressing. This study uses the framework of the cognitive behavioural model of PH to explore DH behaviours, including possible similarities regarding emotional attachment to digital possessions, and possible links with Obsessive Compulsive Disorder (OCD) and indecisiveness. For the study, 282 participants completed an online survey which measured levels of digital and physical hoarding, compulsive acquisition, OCD, indecisiveness and mood. Strong emotional attachments to particular types of digital possessions were evident: this was especially true for photographs and videos. Significant positive relationships were found between all the variables measured. However, a regression analysis revealed that only OCD and PH scores were significant predictors of DH. DH thus appears to share some of the features of PH. Implications, limitations and future research possibilities are discussed.